Don't walk the line—dance it!. Issue 4 (9th October 2018) - Forest, Jerry
Abstract : An 86% reduction in API RP 754 Tier 1 and Tier 2 loss of primary containment incidents has been realized in the 5 years following the development and implementation of Walk the Line by Celanese. Walk the Line originally was shared at the Center for Chemical Process Safety (CCPS) and AIChE Safety & Health Division Global Congress for Process Safety in 2014 to address operator line‐up errors with three groups of Conduct of Operations tools: changing the culture by setting expectations, operational continuity through operating discipline, and operational readiness. This article will provide an update on our effort to eliminate operator line‐up error in industry. It will outline additional steps taken by Celanese and the results as well as highlight how industry came together to improve on a systemic cause of process safety incidents. © 2018 American Institute of Chemical Engineers Process Saf Prog 37: 493–497, 2018